PENGARUH KUALITAS LAYANAN, KEPERCAYAAN MEREK DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN PAKET DATA INTERNET KARTU XL PRABAYAR - Efendi, Bahtiar; Kholunnafiah, Ulya (DFAME Digital Financial Accounting Management Economics Journal, 2023)
This research aims to investigate the influence of service quality, brand trust, and customer satisfaction on customer loyalty in the context of XL Prepaid Internet Data package users. The study involved a sample of 105 respondents, and data were collected through questionnaires that underwent validity and reliability testing, as well as various statistical analyses including F-test, classical assumption testing, normality test, multicollinearity test, heteroskedasticity test, hypothesis testing, t-test, and R-squared analysis. The findings revealed that service quality did not have a significant impact on customer loyalty, whereas brand trust and customer satisfaction had a positive and significant influence on customer loyalty. This research was conducted among XL Prepaid Internet Data package customers in Wonosobo City, contributing to a better understanding of the factors affecting customer loyalty in this industry. The study is relevant in the context of enhancing customer satisfaction and brand development in a competitive market.